Prognostic value of exercise echocardiography in diabetic patients - Sousa, Antônio Carlos Sobral (2009)
Background Coronary artery disease (CAD) is the leading cause of death in diabetic patients. Although exercise echocardiography (EE) is established as a useful method for diagnosis and stratification of risk for CAD in the general population, there are few studies on its value as a prognostic tool in diabetic patients. The purpose of this investigation was to evaluate the value of EE in predicting cardiac events in diabetics. Methods 193 diabetic patients, 97 males, 59.8 ± 9.3 yrs (mean ± SD) were submitted to EE between 2001 and 2006 and followed from 7 to 65 months with median of 29 months by phone calls and personal interviews with patients and their primary physician, and reviewing medical records and death certificates. The end points were cardiac events, defined as non-fatal myocardial infarction, late myocardial revascularization and cardiac death. Sudden death without another explanation was considered cardiac death. Survival free of end points was estimated by the Kaplan-Meier method. Results Twenty-six cardiac events were registered in 24 individuals during the follow-up. The rates of cardiac events were 20.6 and 7% in patients with positive and negative EE, respectively (p < 0.001). Predictors of cardiac events included sedentary lifestyle, with RR of 2.57 95%CI [1.09 to 6.02] (P = 0.03) and positive EE, with RR 3.63, 95%CI [1.44 to 9.16] (P = 0.01). Patients with positive EE presented higher rates of cardiac events at 12 months (6.8% vs. 2.2%), p = 0.004. Conclusion EE is a useful method to predict cardiac events in diabetic patients with suspected or known CAD.